Effect of the L499M mutation of the ascomycetous Botrytis aclada laccase on redox potential and catalytic properties. (1st November 2014) - Osipov, Evgeny; Polyakov, Konstantin; Kittl, Roman; Shleev, Sergey; Dorovatovsky, Pavel; Tikhonova, Tamara; Hann, Stephan; Ludwig, Roland; Popov, Vladimir
<x xml:space="preserve">Abstract</x> Laccases are members of a large family of multicopper oxidases that catalyze the oxidation of a wide range of organic and inorganic substrates accompanied by the reduction of dioxygen to water. These enzymes contain four Cu atoms per molecule organized into three sites: T1, T2 and T3. In all laccases, the T1 copper ion is coordinated by two histidines and one cysteine in the equatorial plane and is covered by the side chains of hydrophobic residues in the axial positions. The redox potential of the T1 copper ion influences the enzymatic reaction and is determined by the nature of the axial ligands and the structure of the second coordination sphere. In this work, the laccase from the ascomycete Botrytis aclada was studied, which contains conserved Ile491 and nonconserved Leu499 residues in the axial positions. The three‐dimensional structures of the wild‐type enzyme and the L499M mutant were determined by X‐ray crystallography at 1.7 Å resolution. Crystals suitable for X‐ray analysis could only be grown after deglycosylation. Both structures did not contain the T2 copper ion. The catalytic properties of the enzyme were characterized and the redox potentials of both enzyme forms were determined: E0 = 720 and 580 mV for the wild‐type enzyme and the mutant, respectively. Since the structures of the wild‐type and mutant forms are very similar, the change in the redox potential can be related to the L499M mutation in the T1 site of the enzyme.